Hero Construction Narrative In A Bug’s Life, The Film - Dhea Restu Pradhana (Universitas Pendidikan Indonesia (UPI), 2013)
The present study entitled Hero Construction Narrative in A Bug’s Life, The Film aims to investigate the film narrative of hero construction. The study employs a descriptive qualitative study with textual analysis approach. The present study adopted Hourihan’s (1997) theory as its major theoretical framework and the language of film theory (Heintz and Stracey, 2006). The study found that the hero construction in the film is presented through three phases there are the initiation phase, the conflict phase and the resolution phase. These phases are also analyzed through the language of the film. They are crafted through the pattern of cause and effect where film characters become the agent of causality. These characters are put in binary opposition to construct the hero in the narrative which is mediated through the language of film, such as camera shots, camera movement and mise en scène. The uses of binary opposition support the delivery of the didactic message in the film, since animation films that focus on hero’s journey are often directed to children.Keywords: Film, Animation Film, Narrative Cinema, Hero Construction, Children’s Literature